Pengaruh Kompensasi Eksekutif terhadap Hutang : Studi pada Perusahaan yang Terdaftar di Indeks Kompas100 - Suherman, Suherman (Jurnal Manajemen dan Kewirausahaan, 2019)
The aim of this research is to determine the effect of compensation received by directors (executives) on debt. Sample of this research covers 47 firms listed on Kompas100 index from 2011 until 2015 (there are 218 observations). Controlling for size of firm, firm growth, profitability, liqudity, and structure of asset, the result shows that compensation positively and significantly affects capital structure. This result implies that executives compensated highly are willing to increase stock price volatility and engage in risk taking decisions. https://doi.org/10.26905/jmdk.v7i1.3107